Development & analysis wind system in Singapore - Zhu, Jun Jun (2014)
The purpose of the project is to simulate a wind energy system model using Lab VIEW. The simulation program can also calculate the annual energy and the costs & benefits of the project. With the rapid increase of the pollution and sharp decline of the energy, renewable energy is played the important role all around the world. Wind Energy is one of the most effective renewable energy. It will greatly reduce the use of fossil fuel. But the wing energy technology is not fully mature and it still exits some risks along with the benefits in the wind energy generation filed. It is important to make a simulation program to analysis the result. The LabVIEW program is useful and easy to operate by the user. Once user selects the location, wind turbines, and parameters of wind energy system, the program will show you the annual energy. The after-tax cash flow and equity payback time by years can also be demonstrated in the program. In the end, the result of the simulation is proved that wind energy is not suitable for Singapore. The low wind speed is a big problem of wind power generation in Singapore.